2021
DOI: 10.3390/molecules26061643
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Materials Properties on Bio-Physical Features and Effectiveness of 3D-Scaffolds for Periodontal Regeneration

Abstract: Periodontal diseases are multifactorial disorders, mainly due to severe infections and inflammation which affect the tissues (i.e., gum and dental bone) that support and surround the teeth. These pathologies are characterized by bleeding gums, pain, bad breath and, in more severe forms, can lead to the detachment of gum from teeth, causing their loss. To date it is estimated that severe periodontal diseases affect around 10% of the population worldwide thus making necessary the development of effective treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 186 publications
0
22
0
Order By: Relevance
“…Endogenous cell homing using appropriate biomaterials can be regarded as a more economic, effective, and safe method for treating patients [80]. Therefore, recent research on biomaterials promoting periodontal regeneration is focusing on cell-free scaffold technologies for endogenous cell recruitment [81][82][83]. Studies have shown that the structural configuration of a scaffold has crucial implications on tissue engineering [83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous cell homing using appropriate biomaterials can be regarded as a more economic, effective, and safe method for treating patients [80]. Therefore, recent research on biomaterials promoting periodontal regeneration is focusing on cell-free scaffold technologies for endogenous cell recruitment [81][82][83]. Studies have shown that the structural configuration of a scaffold has crucial implications on tissue engineering [83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, for regenerative medicine purposes, the electrospinning technique produces flexible three dimensional porous membranes with a suitable structure for wound dressing and also drug delivery [119]. As these membranes regard similarities with the skin and mimic the extracellular matrix milieu, reports in the area of regenerative medicine reveal that these fibers-constituted membranes have been used for periodontal diseases due to its physical structure, which allow the addition of drugs, growth factors, and cells [118][119][120]. Nazarnezhad et al (2020) reported that biodegradable electrospun membranes with the addition of vascular endothelial growth factor; angiopoetin1 (Ang1); transforming growth factor-β (TGF-β1); fibroblast growth factor (FGF) and hepatocyte growth factor (HGF); matrix metalloproteinase (MMPs); plasminogen activator inhibitor-1 (PAI-1) or nitric oxide synthase (NOS) exert effects of: stimulating angiogenesis, permeability and leukocyte adhesion; stabilizing vessels and inhibiting permeability; stimulating extracellular matrix (ECM) production; stimulating angio/arteriogenesis; matrix remodeling, release and activation of growth factors; stabilizing nascent vessels and promoting angiogenesis and vasodilation, respectively [121].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In this regard, for regenerative medicine purposes, the electrospinning technique produces flexible three dimensional porous membranes with a suitable structure for wound dressing and also drug delivery [ 119 ]. As these membranes regard similarities with the skin and mimic the extracellular matrix milieu, reports in the area of regenerative medicine reveal that these fibers-constituted membranes have been used for periodontal diseases due to its physical structure, which allow the addition of drugs, growth factors, and cells [ 118 120 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Cardiac tissue engineering, coupled with regenerative medicine, represents a very useful approach to repair or regenerate damaged tissues or organs and restoring their functions. In the last decades, due to the possibility to design scaffolds with tailored physic-chemical and biomechanical features, biomimetic devices based on synthetic or natural polymers have attracted much interest in this field [ 18 , 19 ]. The design of a performing biomaterial takes advantage of the collaboration of researchers belonging to different scientific areas, from chemistry, physics, and engineering, to technology, biology, and medicine.…”
Section: Introductionmentioning
confidence: 99%